Clarificación del zumo de caña de azúcar mediante temperatura y mucílago de cacao para la obtención de una bebida refrescante - Torres Sacón, Jeniffer Valeria (2021)
The research sought to determine the physical, microbiological and organoleptic effects produced by two percentages of cocoa mucilage (12 and 14) and three pasteurization temperature levels (75, 85 and 95 ºC) as a method of clarifying sugar cane juice for obtaining a refreshing drink. A Completely Random Design (D.C.A.) was applied with a two-factor A * B arrangement. Three repetitions were performed, resulting in 18 experimental units of 500 mL. The physical variables evaluated were suspended solids and pH. The statistical analysis showed significant differences between the treatments, being the T3 (12% of cocoa mucilage at 95ºC) the best because it presented greater clarification with a final average of total suspended solids (SST) of 0.0150 Kg /L. In the pH variable, the T4 treatment presented the lowest mean with a value of 3.86. The results of the microbiological analyzes (fecal coliforms, mold and yeast count) were within the NTE INEN 2337 (2008) standard established for this type of product. Sensory evaluation performed using an affective preference test and analyzed using the Friedman statistical test, ranked T3 as the most preferred among treatments.